Differences in Language Ability and Emotional-Behavioral Problems according to Symptom Severity in Children with Autism Spectrum Disorder - Kim, Heeyeon (Yonsei Med J, 2020)
PURPOSE: The aim of this study was to investigate differences in language ability and emotional-behavioral problems according to the severity of social communication impairments (SCI) and restricted and repetitive behaviors (RRB) in children with autism spectrum disorders (ASD). MATERIALS AND METHODS: We grouped 113 children with ASD aged 3–12 years according to the severity of SCI and RRB, and investigated language differences and emotional-behavioral problems among the severity groups. If differences in language abilities between the groups were observed, they were further subdivided to examine possible predictors of both receptive and expressive language abilities. RESULTS: In cluster analyses using subdomains of the Autism Diagnostic Interview-revised, severe SCI individuals showed lower language ability than their milder counterparts, while RRB showed no differences. Receptive and expressive language in the severe SCI group was negatively predicted by social communication and social motivation, respectively. The severe RRB group showed significantly higher levels of anxiety/distress, somatic complaints, thought problems, attention problems, and aggressive behavior, while the severe SCI group was reported to be more withdrawn. CONCLUSION: The results of this study suggest that the severity of SCI greatly affects language ability. In children with severe SCI, social communication and social motivation negatively predicted receptive language and expressive language, respectively. Children with severe RRB may have more emotional-behavioral problems that require active intervention.